2009
DOI: 10.1152/ajprenal.00364.2009
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial-specific CYP4A2 overexpression leads to renal injury and hypertension via increased production of 20-HETE

Abstract: We have previously reported that adenoviral-mediated delivery of cytochrome P-450 (CYP) 4A2, which catalyzes the synthesis of 20-hydroxyeicosatetraenoic acid (20-HETE), results in endothelial dysfunction and hypertension in Sprague-Dawley (SD) rats (Wang JS, Singh H, Zhang F, Ishizuka T, Deng H, Kemp R, Wolin MS, Hintze TH, Abraham NG, Nasjletti A, Laniado-Schwartzman M. Circ Res 98: 962-969, 2006). In this study, we targeted the vascular endothelium by using a lentivirus construct expressing CYP4A2 under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 57 publications
4
56
0
Order By: Relevance
“…20-HETE is a CYP-derived eicosanoid whose synthesis and actions have been linked to the pathogenesis of hypertension in experimental models and humans (38,42). Numerous reports have demonstrated that the vascular synthesis of 20-HETE increases in experimental models of hypertension; vascular overexpression of CYP4A2-20-HETE synthase leads to hypertension, and inhibition of 20-HETE synthesis results in lower blood pressure (11,28,29,34). 20-HETE exerts powerful biological activities in the vasculature; it constricts smooth muscles, stimulates smooth muscle proliferation and migration, inhibits endothelial nitric oxide synthase, and activates the NF-kB-mediated inflammatory program in the vascular endothelium (3,13,17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20-HETE is a CYP-derived eicosanoid whose synthesis and actions have been linked to the pathogenesis of hypertension in experimental models and humans (38,42). Numerous reports have demonstrated that the vascular synthesis of 20-HETE increases in experimental models of hypertension; vascular overexpression of CYP4A2-20-HETE synthase leads to hypertension, and inhibition of 20-HETE synthesis results in lower blood pressure (11,28,29,34). 20-HETE exerts powerful biological activities in the vasculature; it constricts smooth muscles, stimulates smooth muscle proliferation and migration, inhibits endothelial nitric oxide synthase, and activates the NF-kB-mediated inflammatory program in the vascular endothelium (3,13,17).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which 20-HETE contributes to vascular remodeling are unclear; however, 20-HETE has been implicated in many of the biochemical changes preceding remodeling of the arterial wall. 20-HETE has been shown to contribute to collagen accumulation in kidneys from hypertensive rats overexpressing CYP4A2 protein (11). It has also been shown to exert proinflammatory actions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Native CYP4F2 is predominantly expressed in the kidney and liver, and has high ω-hydroxylation activity to catalyze arachidonic acid to 20-HETE (1-3). 20-HETE promotes hypertension by vasoconstriction (4,5) and attenuates hypertension by the inhibition of ion reabsorption (6,7). The dual effect on regulation of blood pressure is spotlighted in the pathophysiology of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that 20-HETE has two contradictory effects in the development of hypertension (2,3). One is prohypertension resulting from constriction of the small arteries (4,5). The other is anti-hypertension caused by inhibition of sodium reabsorption (6,7).…”
Section: Introductionmentioning
confidence: 99%